Dual-energy CT angiography of the lungs: Comparison of test bolus and bolus tracking techniques for the determination of scan delay - Henzler, Thomas; Meyer, Mathias; Reichert, Miriam; Kriššák, Radko; Haneder, Stefan; Schönberg, Stefan; Fink, Christian (European journal of radiology, 2010)
Objective: To prospectively compare test bolus and bolus tracking for the determination of scan delay of pulmonary dual-energy CT angiography in patients with suspected pulmonary embolism. Materials and methods: 60 consecutive patients referred for CTA for exclusion of PE were randomized either into a test bolus group or into a bolus tracking group. All exams were performed on a 64-channel dual source CT scanner. A standard single-acquisition dual-energy CTA was performed after injection of 100ml Iomeprol 400 followed by a saline chaser of 4ml/s. The scan delay was determined using either test bolus (n=30) or bolus tracking (n=30). Test bolus was performed using an additional 20ml Iomeprol 400 injected with a rate of 4ml/s during acquisition of a series of dynamic low-dose monitoring scans followed by injection of a saline bolus of 20ml using the same flow rate. For DECT angiography of the lungs 100ml Iomeprol 400 was injected with an injection rate of 4ml/s followed by a saline chaser of 20ml using the same flow rate. Attenuation profiles of different vascular segments (pulmonary arteries, pulmonary parenchyma, aorta, all 4 heart chambers) were measured to evaluate the timing techniques. Overall image quality of dual-energy “perfusion” maps and virtual 120kV CTA images was evaluated by two radiologists regarding the present of artifacts. Results: In all patients an adequate and homogeneous contrast enhancement of more than 400 Hounsfield units (HU) was achieved in the different vascular districts. No statistically significant difference between test bolus and bolus tracking was found regarding vessel attenuation or overall image quality. Conclusion: A homogeneous opacification of the different vascular territories and the pulmonary parenchyma as well as a sufficient image quality can be achieved with either bolus tracking or test bolus techniques.